Legal Analysis Of Violations Of The Prudential Banking Principle In Credit: A Perspective On Corruption And Money Laundering Crimes - Bayuaji, Rihantoro; Indriastuty, Dwi Elok (Corruptio, 2024)
This research examined the legal implications of credit defaults in Indonesia, specifically assessing whether cases of payment default or bad debt fell under civil or criminal liability. It also investigated whether fraudulent activities in the credit process constituted predicate offenses, such as corruption, potentially leading to money laundering charges. The research aimed to develop a policy framework for resolving legal disputes related to non-performing banking credit. Employing a normative juridical approach, the research utilized conceptual, statutory, case, and philosophical analyses, drawing upon legal references and case studies to substantiate its findings. The results indicated that the legal resolution of banking credit disputes fell into two primary categories. If bad credit resulted from a violation of the Prudential Principles (the 5C’s), banks as creditors could initiate criminal proceedings by reporting the underlying offenses associated with credit disbursement. Conversely, if bad credit stemmed solely from contractual breaches without elements of illegality, banks could seek redress through civil litigation. Furthermore, instances of fraudulent conduct within the credit process could qualify as predicate offenses, thereby enabling criminal proceedings under the Corruption Criminal Act and the Money Laundering Crime Act.